Pengaruh Kemudahan, Ketersediaan Fitur Dan Manfaat Terhadap Kepuasan Nasabah Pengguna Bsi Mobile Di Kecamatan Ilir Barat Kota Palembang - Zulkarnain, Muhammad; Aurantia Marina; Nur Jumriatunnisah; Nurul Ilma Hasana Kunio (J-EBIS (Jurnal Ekonomi dan Bisnis Islam), 2023)
Technology has an important role in life, and one of them is in the banking world. The technology adopted by banking and useful for providing services to every customer is mobile banking, such as at Bank Syariah Indonesia, namely BSI Mobile. This research aims to determine the effect of convenience, features, and benefits on customer satisfaction with BSI mobile users in Ilir Barat I, Palembang City. The data analysis method used is a quantitative method with data analysis techniques using multiple linear regression equations. Data collection used a questionnaire with a sample size of 75 respondents. The research results showed that the variables of convenience, features, and benefits partially and simultaneously influence customer satisfaction with BSI Mobile users in Ilir Barat District, Palembang City.